Innovations in defence support systems.3 intelligent paradigms in security - emagnino, Paolo; Monekosso, Dorothy N.; Jain, Lakhmi C.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book is a continuation of our previous volumes on Innovations in Defence Support Systems. This book includes a sample of recent advances in intelligent monitoring. The contributions include: Data fusion in modern surveillance · Distributed intelligent surveillance systems modeling for performance evaluation · Incremental learning on trajectory clustering · Pedestrian speed profiles from video sequence · System-wide tracking of individuals · A scalable approach based on normality components for intelligent surveillance · Distributed camera overlap estimation · Multi-robot team for environmental monitoring The book is directed to the security experts, engineers, scientists, students and professors who are interested in intelligent monitoring.
Data fusion in modern surveillance -- Distributed Intelligent Surveillance Systems Modeling for Performance Evaluation -- Incremental learning on trajectory clustering -- Highly Accurate Estimation of Pedestrian Speed Profiles from Video Sequences -- System-Wide Tracking of Individuals -- A Scalable Approach based on Normality Components for Intelligent Surveillance distributed Camera Overlap Estimation -- Enabling Large Scale Surveillance.-Multi-Robot Teams for Environmental Monitoring.
Keywords: Electronic books; Military art and science -- Technological innovations; Electronics in military engineering; Military art and science -- Data processing